2019
DOI: 10.3390/s19143170
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Surface EMG Pattern Recognition for Hand Gestures Based on an Artificial Neural Network

Abstract: In recent years, surface electromyography (sEMG) signals have been increasingly used in pattern recognition and rehabilitation. In this paper, a real-time hand gesture recognition model using sEMG is proposed. We use an armband to acquire sEMG signals and apply a sliding window approach to segment the data in extracting features. A feedforward artificial neural network (ANN) is founded and trained by the training dataset. A test method is used in which the gesture will be recognized when recognized label times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 37 publications
0
70
0
Order By: Relevance
“…Cameras are also used to recognize hand motion [ 9 ], while it is sensitive to the use environment such as background texture, color, and lighting. Surface electromyographic signal (sEMG) is a useful non-intrusive technique for recording the electrical activity produced by muscles through surface sensors placed on the skin, which is a promising candidate for motion detection, gesture recognition and even gesture prediction [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cameras are also used to recognize hand motion [ 9 ], while it is sensitive to the use environment such as background texture, color, and lighting. Surface electromyographic signal (sEMG) is a useful non-intrusive technique for recording the electrical activity produced by muscles through surface sensors placed on the skin, which is a promising candidate for motion detection, gesture recognition and even gesture prediction [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another critical step of human motion classification is the selection of classification technology. Based on the above feature extraction methods, researchers mainly used support a vector machine (SVM), decision tree (DT), random forest (RF), nearest neighbor (KNN), and naive Bayes (NB) to classify human motion [ 27 , 28 , 29 , 30 , 31 , 32 ]. Rohit Gupta et al used a time-domain analysis method to classify the movement of the lower limbs, and concluded that the linear discriminant analysis (LDA) classifier had the highest accuracy, and for different feature subsets, the classification accuracy was between 89% and 99% [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The armband can recognize five kinds of hand movements, including palm extension, making a fist, turning wrist outwards, turning wrist inwards, thumb and middle finger two consecutive clicking. This sEMG sensor is equipped with eight medical grade stainless steel dry electrodes that can achieve eight-channel sEMG data acquisition [3] [4]. This device is easy to use.…”
Section: Introductionmentioning
confidence: 99%